Prejudice, racism, and violence reflected in mary flannery o'connor's short stories collections - Nurhasanti, Sri; , Prof. Dr. C. Bakdi Sumanto; , Dr. Phil. Dewi Candraningrum, M.Ed (2014)
The problems the researcher put forward in her study were; how prejudice, racism, and violence reflected in Mary Flannery O'Connor's short story collections and how the human right abuse happened within the stories. In analyzing the problems, the researcher used several theories of prejudice, racism and violence to unveil the characters' behaviors within the stories. There were eighteen stories that the researcher analyzed. The data were taken from all of those stories themselves and from several references; among others from other researches and thesis or journals related to O'Connor's works. Besides that, the researcher also used several criticisms about O'Connor's works to enrich the data source. From the library research, it was seen that most of the characters in O'Connor's works had the prejudice feeling. Among others, the feeling grew into bigger and larger condition into racism and even those two kinds of characteristics go further into the action of violence. The characteristic of prejudice could be seen from the characters of The Grandmother in the story of "A Good Man is Hard to Find"; Rufus Johnson in the story "The Lame Shall Enter First"; the character of Ruby Turpin in the story of "Revelation" and several more. Next, the racism could be found from the characters of Julian's mother in "Everything that Rises Must Converge", with the character of Mr. Head nor Nelson in the story of "The Artificial Niggers" and several characters in the story of "The Displaced Person", and from the story of "Revelation". The theme violence could be clearly found from the story "A Good Man is Hard to Find" that was the character of "The Misfit". Besides the Misfit, violence could also be found from the character of "Manley Pointer" in the story "Good Country People" and the character of Sarah in the story of "Parker's Back". In summary, prejudice theme in Flannery O'Connor stories cover the prejudice as Jones stated in his theory. Prejudice refers to the negative judgement toward other, whether the memers of a race or religion or the occupants of any other significant social role, held in disregard of the facts that contradict it. What prejudice feeling which the characters of the stories have depict the prejudice of Jones (1972). Furthermore, prejudice feeling later on develop into racism in which Flannery O'Connor also took it as one of the themes she put in her writings. The readers can easily understand that prejudice feeling of the characters in the stories develop into the feeling of racism and even increase into violence. The researcher dicloses those three themes successively.